Hierarchical control strategy for unbalanced voltage in an islanded microgrid - Tianyi Ma; Guangyao Cheng; Xinjun Liu (Технічна електродинаміка, 2016)
When the microgrid is running in an islanded mode, unbalanced loads result in microgrid voltage unbalance. The voltage unbalance factor at the Point of Common Coupling (PCC) is a key parameter in measurement of microgrid power quality. To improve microgrid power quality, many documents utilize micro-source voltage measurement results to help adjust the unbalance factor of microgrid voltage. However, due to line impedance presence, there are differences between micro-source output voltage and PCC voltage. Therefore, it is impossible for a micro-source to control the unbalance factor of PCC voltage with high precision by measuring its own output voltage. Based on equivalent circuit, the present paper analyzes the negative sequence component relationship among micro-source output voltage, line impedance voltage drop, and PCC voltage. It further proposes a hierarchical-control-based method to control the unbalance factor of PCC voltage with high accuracy, and analyzes the impact of secondary control delay on system stability by root locus calculating. Finally, the control strategy is validated in an islanded microgrid system with two micro-sources. The experimental results show the effectiveness and feasibility of the proposed control strategy.